Salbutamol-induced lactic acidosis in status asthmaticus survivor - Vorakamol Phoophiboon; Parima Singhagowinta; Sangdao Boonkaya; Thitiwat Sriprasart (BMC Pulmonary Medicine, 2021)
Abstract Background Salbutamol-induced lactic acidosis is a rare presentation that could manifest in specific clinical context as acute asthmatic attack treatment. An increase of glycolysis pathway leading to pyruvate escalation is the mechanism of hyperlactatemia in β2-adrenergic agonist drug. Case presentation A 40-year-old man who had poor-controlled asthma, presented with progressive dyspnea with coryza symptom for 6 days. He was intubated and admitted into medical intensive care unit due to deteriorated respiratory symptom. Severe asthmatic attack was diagnosed and approximate 1.5 canisters of salbutamol inhaler was administrated within 24 h of admission. Initial severe acidosis consisted of acute respiratory acidosis from ventilation-perfusion mismatch and acute metabolic acidosis resulting from bronchospasm and hypoxia-related lactic acidosis, respectively. The lactate level was normalized in 6 h after hypoxemia and ventilation correction. Given the lactate level re-elevated into a peak of 4.6 mmol/L without signs of tissue hypoxia nor other possible etiologies, the salbutamol toxicity was suspected and the inhaler was discontinued that contributed to rapid lactate clearance. The patient was safely discharged on the 6th day of admission. Conclusion The re-elevation of serum lactate in status asthmaticus patient who had been administrated with the vast amount of β2-adrenergic agonist should be considered for salbutamol-induced lactic acidosis and promptly discontinued especially when there were no common potentials.